Transient flow behaviors of the check valve with different spool-head angle in high-pressure hydrogen storage systems. (February 2022) - Ye, Jianjun; Zhao, Zhenhua; Cui, Junxu; Hua, Zhengli; Peng, Wenzhu; Jiang, Pengcheng
Highlights: The valve spool head pressure is positively correlated with the transient opening time. Compared with the fluid force, the spring force is much lower and can be negligible. Increase the spool-head angle will enhance the impact effect from the hydrogen gas flow. Abstract: The strong collision problem of check valve, caused by the high-pressure hydrogen flow, is one major problem in the high-pressure hydrogen storage systems. Understanding of the transient flow behaviors and the impact of the hydrogen gas flow is important for the safety of check valve in hydrogen storage systems. Based on the transient CFD method and the moving mesh technology, the transient hydrogen flow model for the check valve is established. It has been proved by the comparison between the result of simulation and experiment. The flow characteristics at different moment during the opening process is studied, and the movement of the spool of the check valve is also analyzed. Moreover, several transient hydrogen gas flow models with different spool-head angle are established, and effect of the spool-head angle on the movement performance of the valve spool and flow field characteristics is investigated. The results show that the acceleration, velocity and kinetic energy the spool hits the stopper increase by 7%, 16%, and 33% when the spool-head angle increases from 10° to 50°, which enhance the impact effect of the valve spool. This work obviously has a potential benefit for the structural optimization and application of the check valve in the high-pressure hydrogen storage systems.